1979
DOI: 10.1111/j.1399-0004.1979.tb00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Oculodento‐osseous dysplasia: heterogeneity or variable expression?

Abstract: Oculodento‐osseous dysplasia (ODOD) has been recognised in three South African patients from two kindreds of Dutch descent. Their ocular, nasal, dental and digital stigmata resembled those of previously reported cases, but their cranial hyperostosis and mandibular overgrowth were of much greater degree. In addition, the two survivors had serious neurological complications consequent upon spinal cord compression at the base of the skull and calcification of the basal ganglia. Two of the patients were the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…The authors suggest that all ODDD patients may eventually develop neurological symptoms if they were followed long enough, but another explanation supported by our studies may be that clinical variability in neurological symptoms of ODDD patients is the result of genetic background differences. The genetic background dependent variability of the Shuffler phenotype parallels the variable neurological clinical findings in humans (Beighton et al, 1979;Paznekas et al, 2003). Furthermore, many of the symptoms reported by patients with ODDD may be explained by the Shuffler anatomical de-fects.…”
Section: Conclusion and Relevance To Human Studiesmentioning
confidence: 82%
“…The authors suggest that all ODDD patients may eventually develop neurological symptoms if they were followed long enough, but another explanation supported by our studies may be that clinical variability in neurological symptoms of ODDD patients is the result of genetic background differences. The genetic background dependent variability of the Shuffler phenotype parallels the variable neurological clinical findings in humans (Beighton et al, 1979;Paznekas et al, 2003). Furthermore, many of the symptoms reported by patients with ODDD may be explained by the Shuffler anatomical de-fects.…”
Section: Conclusion and Relevance To Human Studiesmentioning
confidence: 82%
“…Clinical features are summarised in Table 1. Beighton et al [1] describe neurological symptoms in affected cousins. Similar to our first patient, their second patient was delayed in walking and had persisting mobility problems.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Timothy syndrome, the association of 4-5 syndactyly, dysmorphism, cardiac arrhythmia and learning disability, is caused by a Beighton et al [1] Traboulsi et al [14] Pizzuti et al [10] Frasson et al [4] Present cases…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of ODDD cases described in the literature show an autosomal dominant inheritance pattern and high phenotypic variability [Shapiro et al, 1997;Loddenkemper et al, 2002]. Up to date, 11 patients from 6 families with autosomal recessive ODDD have been reported [Gillespie, 1964;Beighton et al, 1979;Traboulsi et al, 1986;Frasson et al, 2004;Pizzuti et al, 2004;Richard- , 2006], but only 2 of these cases were confirmed by molecular analysis. Pizzuti et al [2004] detected the R76H homozygous missense variant in one of these patients, while Richardson et al [2006] defined the R33X homozygous nonsense variant in the GJA1 gene in the second case.…”
Section: Discussionmentioning
confidence: 99%